HBF4‐Catalysed Nucleophilic Substitutions of Propargylic Alcohols. Issue 34 (29th October 2015) - Barreiro, Elena; Sanz‐Vidal, Alvaro; Tan, Eric; Lau, Shing‐Hing; Sheppard, Tom D.; Díez‐González, Silvia
Abstract: The activity of HBF4 (aqueous solution) as a catalyst in propargylation reactions is presented. Diverse types of nucleophiles were employed in order to form new C–O, C–N and C–C bonds in technical acetone and in air. Good to excellent yields and good chemoselectivities were obtained using low acid loading (typically 1 mol‐%) under simple reaction conditions. Abstract : The activity of HBF4 (aq. solution) as a catalyst in propargylation reactions is presented. C–O, C–N and C–C bonds were formed in technical acetone and in air. Good to excellent yields were obtained using low acid loading (typically 1 mol‐%) under mild reaction conditions.